Insights on the Mycobacterium tuberculosis population structure associated with migrants from Portuguese-speaking countries over a three-year period in greater Lisbon, Portugal: Implications at the public health level - Pereira, Catarina (2022)
Tuberculosis among foreign-born patients is a key indicator of country-level epidemiological profiles and, of an increasing concern in Europe given the more intensified migratory waves of refugees. Since Portugal presents a lower immigrant-associated TB incidence rate when compared to other European countries, we sought to characterize the epidemiology and transmission dynamics among the foreign-born population coming from Portuguese-speaking countries that are associated with higher TB incidences. In the present study we analyzed 133 Mycobacterium tuberculosis isolates obtained from foreign-born individuals over a three-year period in Lisbon, Portugal, using molecular epidemiological methods such as spoligotyping and 24-loci MIRU-VNTR. Moreover, all strains were subjected to drug susceptibility testing. The genetic profiles obtained suggest that strain importation from Portuguese speaking countries plays a less important role in TB epidemiology but instead argue in favor of a high degree of penetrance of Portuguese endemic strains to the migrant population, including multidrug resistant strains, which is particularly relevant to active screening programs.